2022
DOI: 10.3390/pharmaceutics14030508
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Nanoparticles (Niodx™) for Radiotherapy Enhancement of Glioblastoma and Other Cancers: An NCI Nanotechnology Characterization Laboratory Study

Abstract: Effective and durable treatment of glioblastoma is an urgent unmet medical need. In this article, we summarize a novel approach of a physical method that enhances the effectiveness of radiotherapy. High atomic number nanoparticles that target brain tumors are intravenously administered. Upon irradiation, the nanoparticles absorb X-rays creating free radicals, increasing the tumor dose several fold. Radiotherapy of mice with orthotopic human gliomas and human triple negative breast cancers growing in the brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…58 Niodx CA exhibited IC 50 values of 0.89 and 5.03 mg NPs/mL against porcine renal proximal tubule (LLC-PK1) and human hepatocarcinoma (Hep G2) cell lines, respectively. 21 Our LNE formulations, however, showed slightly lower IC 50 as well as tested on different cell lines, and the in vivo study did not reveal such toxicities. Furthermore, a cellular uptake experiment was carried out on CTAB-free F2, F5, and F6 formulations bearing 0.2 wt % lipophilic NR dye present in their oily core.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…58 Niodx CA exhibited IC 50 values of 0.89 and 5.03 mg NPs/mL against porcine renal proximal tubule (LLC-PK1) and human hepatocarcinoma (Hep G2) cell lines, respectively. 21 Our LNE formulations, however, showed slightly lower IC 50 as well as tested on different cell lines, and the in vivo study did not reveal such toxicities. Furthermore, a cellular uptake experiment was carried out on CTAB-free F2, F5, and F6 formulations bearing 0.2 wt % lipophilic NR dye present in their oily core.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…Looking into the literature, we found that iodinated vitamin E CA showed a LD 50 of about 0.4 mg I/mL on BNL-CL2 embryonic murine hepatocyte cell lines . Niodx CA exhibited IC 50 values of 0.89 and 5.03 mg NPs/mL against porcine renal proximal tubule (LLC-PK1) and human hepatocarcinoma (Hep G2) cell lines, respectively . Our LNE formulations, however, showed slightly lower IC 50 as well as tested on different cell lines, and the in vivo study did not reveal such toxicities.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…A study was conducted to investigate the properties of iodine-containing nanoparticles that can absorb X-rays and determine the boundaries of the tumour in a fluorescent way. Radiation therapy of the brains of mice with orthotopic human gliomas and triple-negative human breast cancer showed considerable prolongation of their lives when iodine-containing nanoparticles were included (Hainfeld et al, 2022). Studies established the importance of iodine for the animal body, its involvement in the synthesis of thyroid hormones, and the causes of iodine-deficient diseases.…”
Section: Introductionmentioning
confidence: 99%